Sustainable Digital Marketing Drives Consumer Engagement: The Mediating Role of Customer Trust in Indonesian Local Brands - Andi Raina Ananda Herdiyana; Baginda Hamzah; Audrey Michelle Wenny Yolanda (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to examine the mediating role of customer trust in the relationship between sustainable digital marketing (SDM) practices and customer brand engagement among Indonesian local brands. In particular, it investigates how key SDM dimensions, namely transparency and disclosure, social and environmental impact communication, and stakeholder engagement, influence engagement through the development of customer trust in digital contexts. Design/methodology/approach – A quantitative cross-sectional survey design was employed. Data were collected from 150 consumers who have prior experience interacting with Indonesian local brands and have been exposed to sustainability-related digital marketing content. The proposed relationships among the constructs were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding/Results – The findings indicate that all SDM dimensions have positive and significant effects on customer trust, with transparency and disclosure emerging as the most influential determinant. Customer trust also demonstrates a strong and significant effect on customer brand engagement. These results suggest that sustainability-oriented digital marketing practices contribute to engagement through the development of customer trust. Originality/Value – This study advances SDM by positioning customer trust as the central mechanism linking sustainability communication to engagement and provides empirical evidence that SDM operates as a credibility-based signaling system with asymmetric effects across its dimensions in an emerging market context.